Development of a Sustainable Theoretical Framework for a Renewable Based Bathroom Unit - Oye, Toyosi K.; Gupta, Naren; Goh, Keng; Kerrouche, Abdelfateh; Oye, Tosin T. (Environmental Management and Sustainable Development, 2021)
One of the major issues facing the world in the 21st century is climate change. However, sustainability has become a crucial concept to combat extreme consumption of environmental resources. The bathroom has been estimated to be the principal user of environmental resources in United Kingdom households. Therefore, the challenge that how a combined water and energy saving unit in the bathroom will contribute to the sustainability of the houses will remain unresolved. This study challenges and extends existing knowledge on sustainability related to the smart bathroom systems considering social, environmental, and economic principles to achieve a highly efficient water and energy consumption in the bathroom. This study gathers that a range of technological challenges are based on the individual components and technologies in the bathroom and concludes that a holistic approach is required for an effective modelling in the bathroom. This allows the examination of energy and water flows in the complex systems, shaped by various social, economic and environmental forces. The method this study presented adopts conceptual and holistic modelling to design and implement a bathroom unit that is sustainable and smart. This study uncovers the contribution of renewable energy source and smart control technologies in the bathroom and the significant contribution it makes in levels of energy consumption and carbon emissions. These sustainable features are subsequently used to develop framework for sustainable for implementing and evaluation of sustainable bathroom system. This study has established a strong quantitative and qualitative links between three dimensions of sustainability.